Electrical discharge machining of Al (6351) alloy: role of electrode shape. (2016) - Kumar, S. Suresh; Uthayakumar, M.; Kumaran, S. Thirumalai; Parameswaran, P.; Mohandas, E.
In this work, an investigation is made in order to identify the influence of machining parameters such as pulse current (I), pulse on time (Ton ) and pulse duty factor (τ) on the electrical discharge machining (EDM) of aluminium (6351) alloy. The effect of electrode shape viz. circular and square configuration on the machining characteristics namely electrode wear ratio (EWR), surface roughness (SR) and over cut (OC) were analysed. The experimental results revealed that the circular electrode exhibits lower EWR, better surface finish and minimised OC when compared to the square electrode. The surface characteristics of the aluminium alloy machined by both the electrodes are also examined by using scanning electron microscope (SEM). The mechanism of crater formation and the surface texture of the machined area are also discussed.